'Wait! Don't touch me!': Police uniforms, family anxiety, and rituals of purification in the COVID-19 pandemic. (4th March 2023) - De Camargo, Camilla
ABSTRACT: Emblematic power is entrenched in the uniform and bodily image of the police. The COVID-19 pandemic has afforded a new layer of understandings of 'dirty work' with police officers, and has shown how the police uniform is perceived to be an involuntary vehicle for physical contamination and symbolic taint. This article is based on interviews with 18 police officers from 11 UK police forces over the summer of 2020 and explores how the COVID-19 pandemic caused increased fear and anxiety about virus contraction, particularly when officers were not prioritised for testing and vaccinations at the time. The possibility of transmitting COVID-19 to family members motivated officers to treat their uniforms differently, and they undertook purification rituals to mitigate violations of the physical and symbolic space around the body. Fear and anxiety of 'the unknown' is a motivator for discussions about long-term effects of officer well-being, and the significance of learning to prepare for future pandemics.